In-vitro antimicrobial activity of different toothpastes - Gautam, Bikram; Dongol, Elisa; Shrestha, Anima (Journal of Kathmandu Medical College, 2018)
Background: Tooth brushing with toothpaste is the most widely practiced form of oral hygiene. Toothpaste aids to improve oral hygiene and effective plaque removal. A wide range of chemicals, mainly antimicrobial agents, have been added to toothpastes which kill microorganisms by disrupting their cell walls and inhibiting their enzymatic activity. Objectives: The aim of the study was to determine the antimicrobial activity of toothpastes. Methods: Eight (Two herbal and six regular) toothpastes were selected for the study. The study was conducted from October to November 2016 at St. Xavier’s College’s microbiology laboratory. Antimicrobial activity of toothpastes were assessed by measuring inhibition zones by broth dilution method and agar well diffusion method. Results: Minimum Inhibitory Concentration determination by tube dilution method and cup well diffusion method was found to be same. The antimicrobial activity on test organisms was shown by all toothpastes (TH1, TH2, TR3, TR4, TR5, TR6, TR7 and TR8). Antimicrobial activity of all toothpastes were almost the same and was statistically significant (t>0.05) Conclusion: All eight toothpastes aids in lower microbial load. However, no toothpaste showed bactericidal and fungicidal effect against the tested microbes. The toothpaste containing only natural active ingredients were found to be more effective than the toothpaste containing chemical active agent followed by weaker antimicrobial effect given by the toothpaste containing both natural and chemical active ingredient as an antimicrobial agent.